Morphological awareness predicts reading comprehension in first grade students - Sparks, Erin; Metsala, Jamie L. (Frontiers in Education, 2023)
Research examining a role for morphological awareness in first grade students’ reading comprehension is scarce, although it is a well-established predictor for students in mid-to-late elementary school. One question that remains is whether morphological awareness explains unique variance in these young readers’ comprehension after accounting for other oral language skills. In this longitudinal study, we assessed Grade 1 students’ inflectional morphological awareness as a predictor of their concurrent (n = 58) and Grade 2 (n = 55) reading comprehension. When controlling for decoding and vocabulary, Grade 1 morphological awareness explained unique variance in concurrent and subsequent reading comprehension (4 and 5 percent, respectively). In novel analyses that controlled for decoding, vocabulary, and syntactic awareness, morphological awareness explained unique variance in Grade 2 reading comprehension (5 percent), but not in concurrent reading comprehension. This unique contribution only in second grade may be because decoding skills accounted for less of the overall variance in second than in first grade comprehension or due to the expectation that polymorphemic words are more frequent in second grade texts. Overall, morphological awareness emerged as the strongest oral language predictor in all models. These results support morphological awareness’ relevance to reading comprehension from early in children’s reading development and highlight the need for research to further explore the effects of targeting English morphological awareness with young students.